Internet connectivity disruption in Cambodia (Cambodia) - Voidly (2026)
CRITICAL severity mixed detected in Cambodia. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: KH-2026-0026
Keywords: censorship; KH; mixed; critical